A method for preparing a modified asphalt mixture using an organically functionalized retired wind turbine blade material

CN118184224BActive Publication Date: 2026-10-13LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410321845.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-20
Publication Date
2026-10-13
Estimated Expiration
2044-03-20

AI Technical Summary

Technical Problem

[0005]针对现有沥青混合料强度低、稳定性差的问题,本发明提供一种有机官能团修饰退役风机叶片材料制备沥青混合料的方法,通过在退役风机叶片表面修饰有机官能团,提高退役风机叶片材料与沥青混合料的作用力,从而获得性能优异的改性沥青混合料,在提高公路建设强度和稳定性的同时,实现了退役风机叶片规模化、资源化、高值化和绿色化回收再利用

Benefits of technology

1、通过官能团修饰剂在退役风机叶片材料表面修饰有机官能团,提高退役风机叶片材料与沥青混合料的作用力,从而提高改性沥青混合料的强度和稳定性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a method for preparing modified asphalt mixture by using organic functional group modified retired fan blade material, wherein the retired fan blade is crushed first, and then treated by an organic functional group modifier to obtain the organic functional group modified retired fan blade material, so that the acting force between the retired fan blade material and the asphalt mixture is improved, and finally the modified asphalt mixture with excellent performance is obtained and applied to highway construction. In the application, the functional group modifier is used to modify the organic functional group on the surface of the retired fan blade material, so that the acting force between the retired fan blade material and the asphalt mixture is improved, and the obtained asphalt mixture has better performance than conventional asphalt mixture, and the retired fan blade is used in a high value way.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing modified asphalt mixtures by modifying decommissioned wind turbine blade materials with organic functional groups, belonging to the field of solid waste resource utilization technology. Background Technology

[0002] With the rapid development of wind power, the number of retired wind turbine blades is increasing year by year. Data shows that by 2025, my country is expected to generate nearly 5,800 tons of solid waste from retired wind turbine blades, reaching 74,000 tons by 2028. The problem of solid waste from retired wind turbine blades has consistently plagued industry enterprises and hindered the green development of the entire wind power industry. Currently, the main methods for treating retired wind turbine blades include landfill disposal, cement kiln co-processing, chemical dissolution, pyrolysis, and incineration. Landfill disposal occupies land, pollutes the environment, and wastes resources; cement kiln co-processing has difficulty controlling the optimal blending ratio and can easily affect cement quality; chemical dissolution has difficult-to-control reaction conditions and requires complex chemical reagents; pyrolysis and incineration are energy-intensive, costly, and may produce toxic gases such as dioxins. Therefore, achieving large-scale recycling and resource-based, harmless disposal of retired wind turbine blades is urgently needed.

[0003] Asphalt concrete is mainly used in highway construction. In 2020, the total mileage of highways in my country reached 5.2 million kilometers, an increase of 190,000 kilometers compared to the previous year. The continuous growth in highway construction mileage in my country has led to a corresponding increase in market demand for asphalt concrete. In the past five years, my country's asphalt concrete production has steadily increased, from 320 million tons in 2016 to 470 million tons in 2020. However, at present, asphalt concrete pavements suffer from poor stability and low strength. Researchers have found that adding glass fibers can improve the strength and stability of asphalt concrete. For example, CN202310451769.4 discloses a production process for reinforcing asphalt concrete with chopped glass fibers. This process utilizes the hydrolysis and condensation reaction of a treatment solution to improve the surface physicochemical properties of the glass fibers. After modification, the glass fibers have better compatibility with asphalt, and the asphalt is less prone to segregation and bleeding under high-temperature conditions. The high-temperature stability of the mixture is also indirectly and effectively improved, thereby increasing the tensile strength and high-temperature performance of the asphalt mixture. CN202310797420.6 discloses an asphalt mixture and its preparation method. The method involves preparing modified asphalt, modified glass fiber, and a final mixture to obtain an asphalt mixture that improves drainage performance, enhances anti-aging properties, and improves strength stability at different temperatures. However, the aforementioned patents all suffer from high preparation costs and complex preparation processes, hindering the widespread adoption of modified asphalt concrete.

[0004] Decommissioned wind turbine blades are composite materials made of glass fiber and resin, which have the characteristics of high strength, light weight, corrosion resistance, good flame retardancy, and excellent processability. Taking advantage of the above characteristics of decommissioned wind turbine blades, crushing them and adding them to asphalt mixtures can improve the strength and stability of asphalt concrete. This is an effective way to recycle and reuse decommissioned wind turbine blades, and it is also the focus of this invention. Summary of the Invention

[0005] To address the problems of low strength and poor stability in existing asphalt mixtures, this invention provides a method for preparing asphalt mixtures by modifying decommissioned wind turbine blade materials with organic functional groups. By modifying the surface of decommissioned wind turbine blades with organic functional groups, the interaction force between the decommissioned wind turbine blade materials and the asphalt mixture is improved, thereby obtaining a high-performance modified asphalt mixture. This method not only improves the strength and stability of highway construction but also realizes the large-scale, resource-based, high-value, and green recycling and reuse of decommissioned wind turbine blades.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing modified asphalt mixture by modifying decommissioned wind turbine blade materials with organic functional groups includes the following steps: 1) Dissolve the functional group modifier in a solvent, then add the crushed retired wind turbine blade material, react at 50~200℃ for 3~10h, filter and dry to obtain the retired wind turbine blade material modified with organic functional groups. The length of the decommissioned wind turbine blade material after crushing is 0.1~8mm and the diameter is 0.1~8mm.

[0007] The functional group modifier is one or more of the following: sodium dodecyl sulfate, sodium salicylate, sodium dodecylbenzene sulfonate, sodium dioctyl sulfosuccinate, polyoxyethylene ether, polyoxyethylene octylphenol ether-10, polyethylene terephthalate, polyarylate, polyoxyethylene sorbitan fatty acid ester, ethylenediamine, tetraethylammonium bromide, aniline, and hexadecyltrimethylammonium bromide.

[0008] The amount of the functional group modifier added is 0.05~25.0% of the weight of the decommissioned wind turbine blade material, and the functional group modifier is added once or multiple times.

[0009] The solvent is one or more of deionized water, ethanol, ethylene glycol, and acetone, and the amount of solvent added is 0.1 to 20 times the weight of the decommissioned wind turbine blade material.

[0010] 2) Aggregates, mineral powder, organic functional group modified retired wind turbine blade materials and asphalt are mixed evenly at 100~250℃ to obtain modified asphalt mixture; The modified asphalt mixture contains the following components by weight percentage: 0.1-25.0% organic functional group modified decommissioned wind turbine blade material, 0.1-25.0% mineral powder, 30.0-99.7% aggregate, and 0.1-20.0% asphalt. The aggregate is diabase with a particle size range of 0.05-20 mm; the mineral powder is calcium carbonate with a particle size <0.1 mm.

[0011] This invention modifies organic functional groups on decommissioned wind turbine blade materials with functional group modifiers, thereby improving the interaction force between the decommissioned wind turbine blade materials and asphalt mixtures, thus obtaining high-performance modified asphalt mixtures. This improves the strength and stability of highway construction while realizing the large-scale, resource-based, high-value, and green recycling and reuse of decommissioned wind turbine blades.

[0012] Compared with asphalt mixtures prepared from unmodified decommissioned wind turbine blade materials and conventional asphalt mixtures, modified asphalt mixtures prepared from organically functionalized decommissioned wind turbine blade materials exhibit a porosity of 3.0%–4.5%, a mineral aggregate porosity of 17.2%–18.1%, an asphalt saturation of 75%–85%, a Marshall stability of 9.5 kN–11.5 kN, a flow value not exceeding 4 mm, a water immersion Marshall residual stability and a freeze-thaw splitting test residual strength ratio exceeding 95%, and a dynamic stability exceeding 8500 cycles / mm. The strength and stability of the modified asphalt mixture are significantly superior to those of conventional asphalt mixtures and asphalt mixtures prepared from unmodified decommissioned wind turbine blade materials, providing a new approach for the recycling and reuse of decommissioned wind turbine blade materials.

[0013] In summary, the present invention has the following beneficial effects: 1. By modifying the surface of decommissioned wind turbine blade materials with functional group modifiers to enhance the interaction force between the decommissioned wind turbine blade materials and asphalt mixtures, the strength and stability of modified asphalt mixtures are improved. 2. The asphalt mixture prepared by modifying retired wind turbine blade materials with organic functional groups in this invention can meet the various indicators of asphalt mixture, improve the strength and stability of highway construction, and realize the large-scale, resource-based, high-value and green recycling and reuse of retired wind turbine blades. Detailed Implementation

[0014] The following specific embodiments further illustrate the method for preparing modified asphalt mixtures from organic functional group-modified decommissioned wind turbine blade materials, which is not limited to the scope of protection of the present invention.

[0015] Example 1 (1) The preparation steps of organic functional group modified decommissioned wind turbine blade material are as follows: 5.0% (referring to the mass ratio of the decommissioned wind turbine blade material) sodium dodecyl sulfate and 6.0% (referring to the mass ratio of the decommissioned wind turbine blade material) polyoxyethylene sorbitan fatty acid ester are weighed and dissolved in a mixed solution of 0.05 kg ethanol and 0.05 kg deionized water at 100 °C. Then, 1 kg of crushed decommissioned wind turbine blade material is added, reacted at 100 °C for 5 h, filtered, and dried at 60 °C to obtain organic functional group modified decommissioned wind turbine blade material.

[0016] Preparation of modified asphalt mixture: 70.0% aggregate, 10.0% mineral powder, 15.0% organic functional group modified decommissioned wind turbine blade material and 5.0% asphalt are mixed evenly at 160℃ to obtain modified asphalt mixture.

[0017] (2) Asphalt mixture performance test: The modified asphalt mixture prepared above was tested according to the asphalt mixture test method. The results are shown in Table 1.

[0018] Example 2 (1) The preparation steps of organic functional group modified decommissioned wind turbine blade material are as follows: 10.0% (referring to the mass ratio of the decommissioned wind turbine blade material) of hexadecyltrimethylammonium bromide is dissolved in 10 kg of ethylene glycol solution at 140 °C, and then 1 kg of crushed decommissioned wind turbine blade material is added. The reaction is carried out at 140 °C for 7 h, filtered, and dried at 180 °C to obtain organic functional group modified decommissioned wind turbine blade material for later use; Preparation of modified asphalt mixture: 55.0% aggregate, 15.0% mineral powder, 10.0% organic functional group modified decommissioned wind turbine blade material, and 20.0% asphalt are mixed evenly at 200℃ to obtain modified asphalt mixture.

[0019] (2) Asphalt mixture performance test: The modified asphalt mixture prepared above was tested according to the asphalt mixture test method. The results are shown in Table 1.

[0020] Example 3 (1) The preparation steps of organic functional group modified decommissioned wind turbine blade material are as follows: 15.0% (referring to the mass ratio of the decommissioned wind turbine blade material) sodium dodecylbenzenesulfonate and 10.0% (referring to the mass ratio of the decommissioned wind turbine blade material) polyoxyethylene ether are weighed and dissolved in 20 kg ethylene glycol solution at 200 °C. Then 1 kg of crushed decommissioned wind turbine blade material is added, reacted at 200 °C for 3 h, filtered, and dried at 300 °C to obtain organic functional group modified decommissioned wind turbine blade material for later use. Preparation of modified asphalt mixture: 60.0% aggregate, 5.0% mineral powder, 25.0% organic functional group modified decommissioned wind turbine blade material, and 10.0% asphalt are mixed evenly at 250℃ to obtain modified asphalt mixture.

[0021] (2) Asphalt mixture performance test: The modified asphalt mixture prepared above was tested according to the asphalt mixture test method. The results are shown in Table 1.

[0022] Example 4 (1) The preparation steps of organic functional group modified decommissioned wind turbine blade material are as follows: Weigh 15.0% (referring to the mass ratio of the decommissioned wind turbine blade material) ethylenediamine and 10.0% (referring to the mass ratio of the decommissioned wind turbine blade material) polyethylene terephthalate and dissolve them in a mixed solution of 2 kg acetone and 3 kg ethanol at 180°C. Then add 1 kg of crushed decommissioned wind turbine blade material, react at 180°C for 4 h, filter, and dry at 280°C to obtain organic functional group modified decommissioned wind turbine blade material for later use. Preparation of modified asphalt mixture: 30.0% aggregate, 25.0% mineral powder, 25.0% organic functional group modified decommissioned wind turbine blade material, and 20.0% asphalt are mixed evenly at 230℃ to obtain modified asphalt mixture.

[0023] (2) Asphalt mixture performance test: The modified asphalt mixture prepared above was tested according to the asphalt mixture test method. The results are shown in Table 1.

[0024] Example 5 (1) The preparation steps of organic functional group modified decommissioned wind turbine blade material are as follows: Weigh 0.03% (referring to the mass ratio of the decommissioned wind turbine blade material) of polyoxyethylene sorbitan fatty acid ester and 0.02% (referring to the mass ratio of the decommissioned wind turbine blade material) of sodium salicylate and dissolve them in 0.3 kg of ethylene glycol solution at 150 °C. Then add 1 kg of crushed decommissioned wind turbine blade material, react at 150 °C for 8 h, filter, and dry at 220 °C to obtain organic functional group modified decommissioned wind turbine blade material for later use. Preparation of modified asphalt mixture: 75.0% aggregate, 15.0% mineral powder, 5.0% organic functional group modified decommissioned wind turbine blade material and 5.0% asphalt are mixed evenly at 130℃ to obtain modified asphalt mixture.

[0025] (2) Asphalt mixture performance test: The modified asphalt mixture prepared above was tested according to the asphalt mixture test method. The results are shown in Table 1.

[0026] Example 6 (1) The preparation steps of organic functional group modified decommissioned wind turbine blade material are as follows: Weigh 0.3% (referring to the mass ratio of the decommissioned wind turbine blade material) sodium dodecyl sulfate and 1.2% (referring to the mass ratio of the decommissioned wind turbine blade material) sodium salicylate and dissolve them in 3 kg of deionized water at 50 °C. Then add 1 kg of crushed decommissioned wind turbine blade material, react at 50 °C for 9 h, filter, and dry at 160 °C to obtain organic functional group modified decommissioned wind turbine blade material for later use. Preparation of modified asphalt mixture: 53.0% aggregate, 13.0% mineral powder, 22.0% organic functional group modified decommissioned wind turbine blade material and 12.0% asphalt are mixed evenly at 170℃ to obtain modified asphalt mixture.

[0027] (2) Asphalt mixture performance test: The modified asphalt mixture prepared above was tested according to the asphalt mixture test method. The results are shown in Table 1.

[0028] Example 7 (1) The preparation steps of organic functional group modified decommissioned wind turbine blade material are as follows: 7.0% (referring to the mass ratio of the decommissioned wind turbine blade material) sodium salicylate and 8.0% (referring to the mass ratio of the decommissioned wind turbine blade material) sodium dioctyl sulfosuccinate are weighed and dissolved in 4 kg of ethylene glycol at 100℃. Then 1 kg of crushed decommissioned wind turbine blade material is added, and the reaction is carried out at 100℃ for 3 h. After filtration, the filter cake is added to 3 kg of deionized aqueous solution containing 10% (referring to the mass ratio of the decommissioned wind turbine blade material) sodium dodecyl sulfate. The reaction is carried out at 100℃ for 6 h. After filtration, the decommissioned wind turbine blade material modified with organic functional group is obtained and set aside. Preparation of modified asphalt mixture: 73.0% aggregate, 15.0% mineral powder, 2.0% organic functional group modified decommissioned wind turbine blade material, and 10.0% asphalt are mixed evenly at 110℃ to obtain modified asphalt mixture.

[0029] (2) Asphalt mixture performance test: The modified asphalt mixture prepared above was tested according to the asphalt mixture test method. The results are shown in Table 1.

[0030] Example 8 (1) The preparation steps of organic functional group modified decommissioned wind turbine blade material are as follows: Weigh 5.0% (referring to the mass ratio of the decommissioned wind turbine blade material) tetraethylammonium bromide and 5.0% (referring to the mass ratio of the decommissioned wind turbine blade material) aniline and dissolve them in 6 kg of ethanol at 80°C. Then add 1 kg of crushed decommissioned wind turbine blade material and react at 80°C for 4 h. Filter and add the filter cake to 4 kg of acetone solution containing 3.0% (referring to the mass ratio of the decommissioned wind turbine blade material) hexadecyltrimethylammonium bromide and 2.0% (referring to the mass ratio of the decommissioned wind turbine blade material) polyarylate. React at 80°C for 5 h. Filter and dry at 300°C to obtain organic functional group modified decommissioned wind turbine blade material for later use. Preparation of modified asphalt mixture: 54.5% aggregate, 23.0% mineral powder, 22.0% organic functional group modified decommissioned wind turbine blade material, and 0.5% asphalt are mixed evenly at 250℃ to obtain modified asphalt mixture.

[0031] (2) Asphalt mixture performance test: The modified asphalt mixture prepared above was tested according to the asphalt mixture test method. The results are shown in Table 1.

[0032] Comparative Example 1 (1) Preparation of conventional asphalt mixture: Asphalt mixture is prepared using conventional methods.

[0033] (2) Asphalt mixture performance test: The porosity, aggregate void ratio, flow value, Marshall stability, water immersion Marshall residual stability, dynamic stability and other properties of the asphalt mixture prepared above were tested according to the asphalt mixture test method. The results are shown in Table 1.

[0034] Comparative Example 2 (1) Asphalt mixture preparation method: 60.0% aggregate, 20.0% mineral powder, 10.0% unmodified decommissioned wind turbine blade material and 10.0% asphalt are mixed evenly at 160℃ to obtain modified asphalt mixture.

[0035] (2) Asphalt mixture performance test: The porosity, aggregate void ratio, flow value, Marshall stability, water immersion Marshall residual stability, dynamic stability and other properties of the asphalt mixture prepared above were tested according to the asphalt mixture test method. The results are shown in Table 1.

[0036] Table 1. Test results of asphalt mixtures in Examples 1-8 and Comparative Examples 1-2 The test results show that modifying the surface of decommissioned wind turbine blade materials with organic functional groups using functional group modifiers improves the interaction force between the decommissioned wind turbine blade materials and asphalt mixtures, thereby improving the strength and stability of the modified asphalt mixtures. Furthermore, asphalt mixtures prepared using organically modified decommissioned wind turbine blade materials as additives can meet all the required asphalt mixture specifications.

Claims

1. A method for preparing modified asphalt mixtures by modifying decommissioned wind turbine blade materials with organic functional groups, characterized in that, Includes the following steps: 1) Dissolve the functional group modifier in a solvent, then add the crushed retired wind turbine blade material, react at 50~200℃ for 3~10h, filter and dry to obtain the retired wind turbine blade material modified with organic functional groups. The broken, decommissioned wind turbine blade material has a length of 0.1~8mm and a diameter of 0.1~8mm; The functional group modifier is one or more of the following: sodium dodecyl sulfate, sodium salicylate, sodium dodecylbenzene sulfonate, sodium dioctyl sulfosuccinate, polyoxyethylene ether, polyoxyethylene octylphenol ether-10, polyethylene terephthalate, polyarylate, polyoxyethylene sorbitan fatty acid ester, ethylenediamine, tetraethylammonium bromide, aniline, and hexadecyltrimethylammonium bromide; the amount of the functional group modifier added is 0.05~25.0% of the weight of the decommissioned wind turbine blade material. 2) Aggregates, mineral powder, organic functional group modified retired wind turbine blade materials and asphalt are mixed evenly at 100~250℃ to obtain modified asphalt mixture; The modified asphalt mixture contains the following weight percentages of each component: 0.1-25.0% of organic functional group-modified decommissioned wind turbine blade material, 0.1-25.0% of mineral powder, 30.0-99.7% of aggregate, and 0.1-20.0% of asphalt.

2. The method for preparing modified asphalt mixture from organically functionalized decommissioned wind turbine blade material as described in claim 1, characterized in that, The functional group modifier is added once or multiple times.

3. The method for preparing modified asphalt mixture from organically functionalized decommissioned wind turbine blade material as described in claim 1, characterized in that, The solvent is one or more of deionized water, ethanol, ethylene glycol, and acetone, and the amount of solvent added is 0.1 to 20 times the weight of the decommissioned wind turbine blade material.

4. The method for preparing modified asphalt mixture from organically functionalized decommissioned wind turbine blade material as described in claim 1, characterized in that: The aggregate is diabase, and the aggregate particle size range is 0.05~20mm.

5. The method for preparing modified asphalt mixture from organically functionalized decommissioned wind turbine blade material as described in claim 1, characterized in that: The mineral powder is calcium carbonate with a particle size of <0.1mm.

Citation Information

Patent Citations

  • Production process method of asphalt concrete reinforced chopped glass fiber

    CN116715453A

  • Asphalt mixture and preparation method thereof

    CN116514458A

  • Lightweight asphalt mixture prepared from regenerated fan blades

    CN117003511A